Thirty years of research on traumatic brain injury rehabilitation: a bibliometric study - Liu, Yang; Yao, Xiaomeng; Qian, Jinghua (Frontiers in Neurology, 2023)
Background: Traumatic brain injury (TBI) is a major public health concern with far-reaching consequences on individuals' lives. Despite the abundance of works published on TBI rehabilitation, few studies have bibliometrically analyzed the published TBI rehabilitation research. This study aims to characterize current international trends and global productivity by analyzing articles on TBI rehabilitation using bibliometric approaches and statistical methods. Methods: We conducted a bibliometric analysis of data retrieved and extracted from the Web of Science Core Collection database to examine the evolution and thematic trends in TBI rehabilitation research up until December 31, 2022. The specific characteristics of the research articles on TBI rehabilitation were evaluated, such as publication year, countries/regions, institutions, authors, journals, research fields, references, and keywords. Results: The analysis revealed that there were 5541 research articles on TBI rehabilitation, with the number of publications and citations progressively increasing over the years. The United States (US, 2833, 51.13%), Australia (727, 13.12%), and Canada (525, 9.47%) were the most prolific countries/regions, and the University of Washington (226, 4.08%) and Hammond FM (114, 2.06%) were the most productive institution and author, respectively. The top 3 productive journals were Brain Injury (862; 15.56%), Archives Of Physical Medicine And Rehabilitation (630; 11.37%), and Journal Of Head Trauma Rehabilitation (405, 7.31%). The most frequent research fields were Rehabilitation, Neurosciences, and Clinical Neurology. Co-citation references mainly covered aspects of outcome assessment, community integration and management, and “injury chronicity” and “sequelae” have gained more attention in recent years. “TBI,” “rehabilitation,” “brain injuries,” “mild TBI” and “outcome” were the most commonly used keywords. The analysis also revealed emerging research subjects, such as "return to work," "disorder of consciousness," "veterans," "mild traumatic brain injury," "pediatric," "executive function," "acquired brain injury," "occupational therapy," and " posttraumatic stress disorder." Conclusion: This study provides valuable insights into the current state of TBI rehabilitation research. Attention to research in TBI rehabilitation has rapidly increased in the last three decades. TBI rehabilitation research is characterized by its multi-disciplinary approach. The analysis revealed emerging research subjects that could inform future research directions.